BAGAIMANA MENANAMKAN PENDIDIKAN NILAI PADA ANAK-ANAK ? - Purwanti, Isti Yun (Paradigma, 2015)
It is not easy to teach value education to children. Both educators and parents have to pay attention to and take account of children’s development tasks. Children are different from adolescents and adults so that the diction used in teaching them values must be appropriate and suitable to their development tasks. Educators should understand children’s physical and psychological conditions to teach them values. With respect to this background, this article attempts to investigate ways to inculcate values in children. Teaching value education to children cannot employ only one method but needs a variety of methods in accordance with their development tasks and must be done in a longitudinal manner. Children should recognize and understand what values mean and this should be done not only by formal schools but also by all involved parties including parents and the surrounding environment. The following will explain some methods to inculcate values in children in accordance with their development tasks. One of the methods that educators can employ is playing. Playing can be influential in inculcating values in children because it includes rules, discipline, autonomy, cooperation with groups, responsibility, and introduction to norms that they have to follow. Through playing, children will learn to recognize rules, discipline, responsibility, and autonomy, and to adapt themselves with the environment. Playing is an activity that helps children attain their full development in the physical, intellectual, social, moral, and emotional aspects. Besides playing as described above, the Living Values : An Educational Program (LVEP) method, another method that is being applied, is also presented in this article. The LVEP method is a program to introduce and inculcate values in children through telling stories, singing songs, having discussions, and doing activities that support to create the expected conditions. Meanwhile, the materials included in the program are the peace unit, the respect unit, the love unit, the responsibility unit, the happiness unit, the cooperation unit, the honesty unit, the modesty unit, the tolerance unit, the humbleness unit, and the unity unit. The materials are taken from the twelve universal values formulated by the UNO. Key words: value education, children